Detection of IncN‐pST15 one‐health plasmid harbouring blaKPC‐2 in a hypermucoviscous Klebsiella pneumoniae CG258 isolated from an infected dog, Brazil. Issue 6 (21st February 2021) - Sellera, Fábio P.; Fuga, Bruna; Fontana, Herrison; Esposito, Fernanda; Cardoso, Brenda; Konno, Sibele; Berl, Carla; Cappellanes, Mariana H.; Cortez, Marcia; Ikeda, Marcelo; de Souza, César M.; Cerdeira, Louise; et al.
Abstract: The emergence and rapid spread of carbapenemase‐producing Enterobacterales represents a serious public health concern. Critically, these global priority bacteria have begun to be reported in companion animals, implying a potential risk of cross‐transmission between humans and pets. Using long‐read (MinION) and short‐read (Illumina) sequencing technologies, we have identified and characterized a hypermucoviscous KPC‐2‐producing Klebsiella pneumoniae strain belonging to the high‐risk international clone ST11/CG258, in a dog with urinary tract infection. Strikingly, the bla KPC‐2 gene was carried by a 54‐kb IncN plasmid assignated to ST15, which shared 99.8 and 96.8% pairwise identity with IncN‐pST15 plasmids from human and environmental K. pneumoniae strains, respectively; all come from an area with high endemicity of KPC‐2. Our findings suggest that IncN‐pST15 plasmids conferring carbapenem resistance can play as important a role as clonal transmission of K. pneumoniae, representing another major challenge for One Health.